Supercharging Strategies for Prefabricated Flaps in a Rat Model - Xu, Heng; Steinberger, Zvi; Wo, Yan; Li, Ke; Kuo, Chenghung; Tong, Yun; Zhang, Yixin (Journal of Reconstructive Microsurgery, 2019)
Background Limited survival area is an intractable problem in the clinical practice of prefabricated flaps. This study compared four strategies to find an effective method and to understand the potential mechanisms for supercharging.Methods A prefabricated abdominal flap rodent model was prepared. Rats were randomly divided into five groups (n = 6/group). (A) Control group: prefabricated right side femoral vessels. Based on group A, various prefabricated vessels were added; (B) proximal venous supercharging group: right side superficial inferior epigastric vein (SIEV); (C) proximal arterial supercharging group: right side superficial inferior epigastric artery (SIEA); (D) distal venous supercharging group: left side SIEV; and (E) distal arterial supercharging group: left side SIEA. Macroscopic analysis, near-infrared fluorescence imaging, and microscopy were used to analyze the survival area, fluorescence area, and capillary density.Results No significant differences in survival areas were found among supercharging groups (B–E), which were larger than in the control group. Near-infrared fluorescence imaging showed the areas of control and venous supercharging groups (A, B, and D) were smaller than in arterial groups (C and E). Capillary density areas in the right part of the flap in proximal supercharging groups (B and C) and left part of the flap in distal supercharging groups (D and E) were all greater than group A, with no significant differences among the other groups.Conclusion Enhanced neovascularization is a useful supercharging strategy. Both arterial and venous vessel supercharging improved the survival area of prefabricated flaps.
Keywords: prefabricated flaps; microcirculation; supercharging